THE ROLE AND IMPACT OF INFORMATION TECHNOLOGY DEVELOPMENT ON THE STUDENT LEARNING PROCESS IN THE DIGITAL ERA - Pangaribuan, Gunawan; Rafles, Melkisedek; Sihotang, Ester; Tomubolon, Dulles; Marbun, Mutiha; Aritonang, Augus; Napitupulu, Sotarduga; Demario, Diary; Primus, Bernadus; Lengkong, Regina; Sinaga, Dameria (Universitas Mercu Buana, 2025)
The rapid evolution of information technology (IT) has profoundly reshaped the educational landscape, particularly for university students. Learning processes, once confined to physical classrooms, are now accessible through diverse digital platforms with enhanced flexibility. This study aims to analyze the role and impact of IT development on the effectiveness of student learning in the digital age. Employing a literature review methodology drawing from various academic sources and scholarly articles, the findings indicate that IT plays a crucial role in facilitating information access, enhancing learning interactivity, and broadening students' intellectual horizons. Nevertheless, the advancement of IT also introduces negative consequences, such as device dependency, diminished academic focus, and the risk of information misuse. This paper explores both the advantages and the challenges, providing a comprehensive overview of IT's dual role in modern higher education